Shashka in late XIX – XX c.: An Outline of Russian Combat Techniques - Urazbakhtin, Ruslan (Acta Periodica Duellatorum, 2020)
In the late XIX c., when most Western European armies in the discussion about cut and thrust strikes finally gave priority to a thrust, Russian Imperial Army adopted Eastern weapon – shashka, with Caucasian and Asian origins. Despite its late adoption and not Russian origins, shashka quickly became a national weapon. It transformed a lot under the influence of Western European saber. It dislodged all other long-bladed weapons in Russian army and even in the national memory so that nowadays average Russian calls all curved blades “shashka”. This weapon became a symbol of Russian Cossacks and all late Russian cavalry, almost the last long-bladed weapon used at war. This article is aimed to study techniques of fencing on shashkas of Russian Cossacks and soldiers in XIX – XX c., well-preserved in fencing and cutting manuals, as well as army statutes of this period. The author makes an attempt to verify the popular idea that shashka was not used for fencing at all, that it was designed only for cutting and smashing, without any parades, thrusts, feints, tactics. At the beginning of the article a weaponological review of shashka is done. Its distinctive features, origins, types, characteristics are considered.